Whole Blueberries Improve Pain, Functionality, Inflammation, and Cartilage Metabolism in Individuals with Symptomatic Knee Osteoarthritis (FS15-03-19). (13th June 2019) - Du, Chen; Smith, Amy; Avalos, Marco; South, Sanique; Crabtree, Keith; Wang, Wanyi; Kwon, Young-Hoo; Vijayagopal, Parakat; Juma, Shanil
Abstract: Objectives: The purpose of this study was to examine the effect of freeze dried whole blueberry powder on pain, gait performance, joint flexibility, mobility, and serum and urine biomarkers of inflammation and cartilage metabolism in men and women aged 45–79 years old with symptomatic knee osteoarthritis (OA). Methods: In a randomized, double-blind control trial, a total of 63 adults with symptomatic knee OA, were randomized to either consume 40 grams freeze-dried blueberry powder (FDBP) (n = 33) or placebo powder (n = 30) daily for 4 months. Functionality and biomarkers of inflammation and cartilage metabolism were evaluated at baseline, 2 months and 4 months. Western Ontario McMaster Osteoarthritis Index (WOMAC) questionnaires were used to assess pain, and a GAITRite® electronic walkway was used to evaluate gait spatiotemporal parameters. Flexibility of the afflicted joint(s) were assessed via range of motion (ROM). Plasma was assessed for biomarkers such as glycoprotein-39 (YKL-40), insulin-like growth factor-1 (IGF-1), insulin-like growth factor-binding protein (IGFBP)-3, and interleukin (IL)-13. Results: A total of 49 participants completed the study. WOMAC total score and sub-groups including pain, stiffness, and difficulty to perform daily activities decreased significantly in the FDBP group, while no changes of WOMAC total score and difficulty to perform daily activities were observed in the placebo group. Normal walking pace single support percentage for both limbs increased, while double support percentage for both limbs decreased in the FDBP group. ROM increased slightly for both knees in the FDBP treatment group. The FDBP group had an increasing trend in concentrations of IGF-1 with consistently stable concentrations of IGFBP-3, while the placebo group had declining concentrations of IGF-1 and increases in IGFBP-3 over the course of the study. The FDBP group had an overall decrease in the concentration of YKL-40. Also, an increasing trend for IL-13 was observed in the FDBP group. Conclusions: The findings of the study suggest that blueberries may have a positive effect on joint health by reducing pain, stiffness, and difficulty to perform daily activities, while improving gait performance, possibly improving ROM, and slowing down cartilage breakdown as reflected by the changes in the biomarkers. Funding Sources: US Highbush Blueberry Council.